The Docking Protein Cas Links Tyrosine Phosphorylation Signaling to Elongation of Cerebellar Granule Cell Axons - Huang, Jinhong (The American Society for Cell Biology, 2006)
Crk-associated substrate (Cas) is a tyrosine-phosphorylated docking protein that is indispensable for the regulation of the actin cytoskeletal organization and cell migration in fibroblasts. The function of Cas in neurons, however, is poorly understood. Here we report that Cas is dominantly enriched in the brain, especially the cerebellum, of postnatal mice. During cerebellar development, Cas is highly tyrosine phosphorylated and is concentrated in the neurites and growth cones of granule cells. Cas coimmunoprecipitates with Src family protein tyrosine kinases, Crk, and cell adhesion molecules and colocalizes with these proteins in granule cells. The axon extension of granule cells is inhibited by either RNA interference knockdown of Cas or overexpression of the Cas mutant lacking the YDxP motifs, which are tyrosine phosphorylated and thereby interact with Crk. These findings demonstrate that Cas acts as a key scaffold that links the proteins associated with tyrosine phosphorylation signaling pathways to the granule cell axon elongation.